Regarding the debate on genetically modified seeds and the right to use them in Argentina (Huellas, 2024)
The objective of this article is to delve into the debates, practices, and discourse regarding genetically modified seeds and the right to use them in Argentina. Methodologically, it is based on a qualitative perspective and a flexible design that allows for the use of both secondary and primary data. The analysis reveals that the discourse on the use of genetically modified (GM) seeds are mediated by misinformation regarding laws, royalties, and usage rights. Contradictions are observed between the "need for technology" and its payment, and it is evident that the changes introduced by scientific agriculture have significantly impacted agricultural production and organization in Argentina. The conclusion is that the lack of clear and precise information benefits seed companies and perpetuates a production model based on market logic. Promotion of alternative forms of production that are more environmentally and health-friendly is needed, to overcome the exclusive socio-spatial heritage to ensure equitable access to resources.